Achieving Diverse Cover Crop Mixtures: Effects of Planting Date and Seeding Rate. (1st January 2017) - Murrell, Ebony G.; Schipanski, Meagan E.; Finney, Denise M.; Hunter, Mitchell C.; Burgess, Mac; LaChance, James C.; Baraibar, Barbara; White, Charles M.; Mortensen, David A.; Kaye, Jason P.
Abstract : Cover crop mixtures retain higher diversity when allowed sufficient growth in fall. Cereal rye dominates mixtures in spring, particularly when fall planting is delayed. Grasses overperform in cover crop mixtures compared to their growth in monoculture. Brassicas underperform in cover crop mixtures compared to their growth in monoculture. Legumes' growth in cover crop mixtures varies depending on species and planting time. Cover crop mixtures may provide greater diversity of benefits than monocultures. To develop management principles to establish diverse cover crop mixtures, we conducted a 3‐yr study in which monocultures and mixtures of six cover crop species (cereal rye [ Secale cereale L.], oat [ Avena sativa L.], common medium red clover [ Trifolium pratense L.], Austrian winter pea [ Pisum sativum L.], forage radish [ Raphanus sativus L.], and winter canola [ Brassica napus L.]) were planted in a wheat ( Triticum aestivum L.)–maize ( Zea mays L.)–soybean [ Glycine max (L.) Merr.] rotation after wheat (AW) and after maize (AM). Post‐emergence stand counts and aboveground biomass in fall and spring were measured by species for all cover crop treatments. All species planted manifested in monocultures and mixtures in fall, though oat dominated and red clover, canola, and radish underperformed in mixtures. Cereal rye had the highest spring biomass in all mixtures, especially AM. Pea spring biomass was disproportionally greater in relation to seeding rate in the six‐species mixture (6 Spp.) than in monoculture when planted AW. A four‐species mixture (4 Spp.) planted AW retained the highest diversity after overwintering in two of the three planting years. Our study demonstrated that (i) cover crop mixtures retain higher diversity when allowed sufficient growth in fall; (ii) cereal rye dominates mixtures in spring, particularly when fall planting is delayed; (iii) grasses overperform in mixtures compared to their growth in monocultures; (iv) brassicas underperform in mixtures vs. monocultures; and (v) legume growth in mixtures depends on species and planting time.